Авторські словотвірні новотвори в поетичному дискурсі Ліни Костенко - Власенко, В.В.; Османова, З.С. (Культура народов Причерноморья, 2013)
Стаття присвячена лінгвістичному аналізу авторських словотвірних новотворів у поезії
Ліни Костенко. Схарактеризовано їх семантику, словотвірні особливості та стилістичну роль.
Виявлено емоційно-експресивну й оцінну функції авторських новотворів у поетичному контексті.
З’ясовано, що новотвори є важливим стилетворчим, образним елементом поетичного дискурсу. Ці,
оказіонального характеру лексичні одиниці, органічно вплітаються в художню тканину творів і є
виразною ознакою індивідуального стилю авторки. Статья посвящена лингвистическому анализу авторских словообразовательных
неологизмов в поэзии Лины Костенко. Охарактеризовано их семантику, словообразовательные
особенности и стилистическую роль. Выявлено эмоционально-экспрессивную и оценочную функции
авторских новообразований в поэтическом контексте. Обнаружено, что новообразования являются
важным образным элементом поэтического дискурса. Эти, оказионального характера лексические
единицы, органично вплетаются в художественный мир призведений и являются характерным
признаком индивидуального стиля автора. The article is dedicated to linguistic analysis of author’s neologisms in the poetry by Lina Costenko.
The article deals with the lexical and semantic characteristics of individual-author words in poetry Lina
Costenko. The semantical peculiarities of lexical neologisms and the results of word-building in the texts of Lina
Costenko also are being analyzed in the article with the aid of linguistic methodes. On the base of lexical and
semantical analysis of author’s word their most significant groups were distinguished and also the ways of
realization of semantic nuances were retracted. It was found that for the grammatical characteristics the new
words introduce four parts of speech: noun, adjective, verb and adverb. The author create a noun innovation
more active. The tematic group of occasionalisms, certain the dominant lexical-semantic groups and its numeral
and quality staff established. It was identified that author neologisms are important element of writing; they
characterized individuality of author, among of them remain in using of poet and characterized creative style.
It’s using determined the peculiarities of his idiopoetic system and his individual poetic vocabulary.